EXPLORING DIGITAL FINANCIAL LITERACY AND SERVICES KNOWLEDGE: A COMPREHENSIVE STUDY AMONGST COLLEGE STUDENT - S, Dheepiga; Kumar, N. Siva (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the importance of digital financial literacy among college students, particularly in the wake of the COVID-19 pandemic, which has intensified financial challenges. As digital services become increasingly prevalent, understanding college students’ awareness and knowledge of digital financial services is crucial for improving financial literacy in the digital age. A sample of 200 college students was selected through convenient sampling. Data were collected and analyzed using SPSS software to assess their knowledge of and engagement with digital financial services. The research aims to explore the extent of students’ digital financial knowledge and their need for digital financial services. The study identifies current levels of awareness among college students regarding digital financial literacy, highlighting knowledge gaps and areas where improvement is needed. By examining these gaps, the research aims to provide actionable insights for enhancing financial education among students in the digital era. The findings will inform strategies for improving digital financial literacy programs, ensuring that students are better equipped to navigate and utilize digital financial platforms. These insights can help educational institutions and policymakers develop more effective financial education initiatives. This study uniquely focuses on digital financial literacy among college students, an area of increasing importance in today’s digital age. It offers new insights into students’ awareness and knowledge gaps, contributing to the broader understanding of financial literacy in a digital context.